Laparoscopic sleeve gastrectomy for morbidly obese children and adolescents in Saudi Arabia - Kashha, Ahmad M.; Mirza, Abdurrahman F.; Alzebedi, Hassan H.; Kashha, Salim M.; Assiri, Ali M.; Alghamdi, Hashim A. (International Surgery Journal, 2024)
Background: In this study, laparoscopic sleeve gastrectomy results for pediatric and adolescent patients with morbid obesity over a 4-year period at Maternal and Children Hospital in Abha, kingdom of Saudi Arabia were reported. Methods: A study reviewed data on 15-year-old or younger Patients who underwent laparoscopic sleeve gastrectomy to manage morbid obesity. Demographics, clinical characteristics, complications, BMI, and symptom resolution were collected from medical records from 2017-2020. Data was obtained from patients' medical records. Results: Our study showed Postoperative complications occurred in one patient (2.6%), and gallbladder stones were observed in three patients (7.9%), while gastritis was reported in two patients (5.3%). The BMI changes at 6, 12, and 24 months were -7.49, -14.00, and -20.20 kg/m2, respectively, and the percentage changes in BMI were -16%, -30.69%, and -44.28%. The resolution of symptoms and comorbid diseases was 100% for respiratory symptoms and obstructive sleep apnea, 71.4% for musculoskeletal symptoms, 50% for bronchial asthma and diabetes mellitus, and 25% for hypothyroidism. Conclusions: Laparoscopic sleeve gastrectomy is a safe and effective method for treating morbidly obese children and adolescents. It achieves considerable weight loss and comorbidity resolution with a low risk of consequences.